Two Kinds of External Possession in Mississippi Choctaw. (8th October 2020) - Tyler, Matthew
Abstract: External possession refers to the phenomenon where a DP is marked as an independent argument in its clause but is interpreted as the possessor of another argument. Choctaw makes extensive use of external possession, but, puzzlingly, it comes in two distinct morphological profiles. Previous work has assumed these to be surface morphological variants, but this article shows instead that external possession in Choctaw is derived by two distinct mechanisms. One mechanism involves building a DP with an internal possessor and raising the possessor out to a higher, left‐peripheral position. The alternative mechanism involves building two unconnected DPs, one in an internal‐argument position and one in a high applicative phrase, and identifying the higher DP with the possessor θ role of the lower DP in the process of semantic composition, by a mechanism known as delayed saturation . I demonstrate that this latter mechanism can generate external possession of objects and unaccusative subjects, depending on whether there is an external argument, and is subject to a host of interpretative restrictions that the movement‐based mechanism is not. Thus I show not only that external possession can be derived by two different mechanisms but also that those mechanisms may coexist in the same language.